Dynamics of use and land cover in the Rio Pardo valley, Rio Grande do Sul - Schroder, Thomas; Pereira, Rudiney Soares; Zimmermann, Anna Paula Lora; Redin, Cristina Gouvêa; Fleck, Marciane Danniela; Machado, Leonardo Mortari; Rocha, Nájila Souza (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The aims of this study were to evaluate rates of deforestation and forest regeneration in the time span between 1990 and 2014, furthermore to estimate land cover and use by the year of 2018 in the Rio Pardo Valley region. Landsat images were used for land cover and use classification and Dinamica EGO software was used to provide real and estimated transitions among land cover and use classes. Forested area increased at a rate of 0.58% by year. However, the rates of deforestation and forest regeneration are larger, between 3 and 6%. The model developed showed to be consistent throughout the study time span. The land cover and use map estimated for 2018 shows regions which are susceptible to deforestation and should be closely watched by local authorities.